PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN KOMUNIKASI ILMIAH PESERTA DIDIK PADA MATERI PERUBAHAN LINGKUNGAN DI SMAN 2 SUNGAI PENUH - Rohadatul Aisya, Dini; Razak, Abdul; Arsih, Fitri; Olvia Rahmi, Fitri (Universitas Cokroaminoto Palopo, 2024)
This research aims to determine the effect of the model Problem Based Learning on students’ scientific communication skills on environmental change material at SMAN 2 Sungai Penuh. This type of research is Quasi experimental research, with research randomized posttest only control group design. Sampling is carried out using techniques purpose sampling, class X I and class X J were selected as research samples. Data analysis techniques are normality test, homogeneity test, and hypothesis test using independent sample t-test. Based on research, it was found that the result of scientific communication skills of experimental class students were higher than those in the control class. Hypothesis test result can be seen from value tcount > ttable. Based on the hypothesis test, it can be concluded that the model Problem Based Learning influence on students’ scientific communication skills on environmental change material at SMAN 2 Sungai Penuh.